MANAJEMEN BERBASIS SEKOLAH (ORIENTASI BARU PENGEMBANGAN MUTU PENDIDIKAN DASAR DI ERA OTONOMI DAERAH) - Priatna, Asep (STKIP Subang, 2015)
One of the things implied by the education decentralization policy is to run independent school education management in different perspectives according to the conditions of each region. Decentralization is no longer seen as a concept but should be implemented at all levels of management, not least on the institutional arrangements, systems and educational units, both in the formal and non-formal education channels. New patterns of management education in the form of School Based Management, is actually giving ample space for the community that any decision made by the local government is more